’This is VJY, Over’: The Contribution of High Frequency Radio to the Social and Economic Development of the Northern Territory - Bandias, Susan Elizabeth; Mason, Elizabeth (Janie) (Journal of Telecommunications and the Digital Economy, 2019)
This paper examines the relationship between the use of High Frequency (HF) radio and the development of social capital in the Northern Territory (NT) of Australia. Social capital is an elusive concept. It has its origin in a number of disciplines and, as a consequence, it is a mix of disparate and intangible concepts such as trust, reciprocity, norms and cooperation. It has been argued that there is a strong positive correlation between the acquisition of social capital and social and economic wellbeing. In order to determine if the use of HF radio promoted the development of social capital, qualitative data was collected from 32 NT self-identified HF radio users. Although manned operations of the Darwin-based HF coastal radio service ceased on 30 June 2002, the evidence indicates that HF radio was instrumental in the development of a sense of community amongst its widely dispersed and isolated users. The social capital outcomes of HF radio use that included social and economic well-being, engagement in participatory democracy and the acquisition of human capital were precipitated by the shared community concept of trust, informal and formal networks and cross-cutting ties.